Membrane surface modification to enhance membrane hydrophobicity - Goh, Weiming. (2010)
Membrane distillation (MD) is an emerging technology which is being studied as a low cost, energy saving alternative to conventional separation process such as distillation and reverse osmosis for seawater desalination. However, the MD technology has not be used for practical applications in industries due to some barriers which include membrane pore wetting, low permeate flux and flux decline. Therefore, extensive studies on these aspects are being carried out worldwide, aiming on improving MD performance. This report documents the modification of commercial membranes to improve its hydrophobicity and change its pore structure for better application in the MD process.